Pengaruh Bahan Pengganti Sebagian Semen Terhadap Sifat Fisik Beton Dengan Menggunakan Abu Ampas Tebu - Saputra, Yoga Aris; Djauhari, Zulfikar; Novan, Andre (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study examines the influence addition of sugar cane’s ash as a cement substitution material in concrete mixtures to the compressive strength, porosity and concrete shrinkage. Sugarcane ash used in this study came from Lawang, Matur, Agam Regency, West Sumatra. The percentage of sugarcane ash used as substitute material was 0%, 2.5% and 5% from the weight of cement. For the specimen containing 2,5% of sugar cane’s ash, the concrete compressive strength at 28 days was 29.61 Mpa, followed by sugar cane’s ash 5% was 28,86 MPa. Lowest compressive strength occurs in normal concrete of 28,44 MPa. In porosity test of the concrete the lowest value occurred in 2.5% sugarcane ash with a value of 9.71% at the age of 28 days, followed by sugar cane’s ash concrete porosity 5% was 11,73%. The largest porosity value occurs in normal concrete of 11,92%. The value of this porosity shows that the use of sugarcane ash at a percentage of 2.5% can increase the compressive strength of concrete. In concrete shrinkage testing, the results of the direct measurement test obtained the highest shrinkage value in normal concrete of 53 μm. The lowest shrinkage occurs in sugar cane’s ash concrete 5% was 45 μm, and sugar cane’s ash 2,5% of 50 μm.Keywords: sugarcane ash, compressive strength, porosity, concrete shrinkage